Conservation Subdivision: Design Phase – Location of Conserved Open Spaces - Mark E. Hostetler (EDIS, 2010)
WEC276, a 5-page illustrated fact sheet by Mark Hostetler, focuses on decisions made in the design phase — what percentage of the site will be conserved as open space and where to locate it so as to maximize biodiversity values. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, December 2009.